2008
DOI: 10.1167/iovs.08-1811
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Klf4 Target Genes Reveals the Molecular Basis of the Diverse Regulatory Roles of Klf4 in the Mouse Cornea

Abstract: Functionally diverse candidate Klf4 target genes were identified, revealing the molecular basis of the diverse aspects of the Klf4CN corneal phenotype. These results establish Klf4 as an important node in the genetic network of transcription factors regulating the corneal homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 69 publications
7
93
0
Order By: Relevance
“…KLF4 is expressed in differentiated, nonproliferating cells, where it serves to suppress proliferation. Gene expression profiling experiments show that KLF4 suppresses expression of proliferation-associated genes and activates expression of differentiation-associated genes (2)(3)(4)(5). KLF4 has an important regulatory role in epithelia.…”
Section: Klf4mentioning
confidence: 99%
See 1 more Smart Citation
“…KLF4 is expressed in differentiated, nonproliferating cells, where it serves to suppress proliferation. Gene expression profiling experiments show that KLF4 suppresses expression of proliferation-associated genes and activates expression of differentiation-associated genes (2)(3)(4)(5). KLF4 has an important regulatory role in epithelia.…”
Section: Klf4mentioning
confidence: 99%
“…KLF4 activates expression of cyclin-dependent kinase inhibitors (2,13,14) and cooperates with p53 to increase p21…”
Section: Klf4mentioning
confidence: 99%
“…KLF4, therefore, joins an increasingly long list of regulators that are kept at bay in the lower skin layers by p63's direct negative control. Transcriptional profiling has been performed by overexpressing KLF4 in the colon cancer cell line RKO and in an elegant system of corneal cells derived from KLF4-conditional null mice (Swamynathan et al, 2008): this latter study, in particular, reported notorious targets of p63, such as c-Jun and PDGFb-RII, among genes upregulated by KLF4, and FGF-R2, Id2 and C/EBPd, among the repressed ones. The latter is particularly interesting, as it was placed upstream of p63 in the regulation of stem cells of the corneal limbus (Barbaro et al, 2007), and targets of C/EBPd, such as Desmocollin 3 and other genes coding for desmosomal proteins (Smith et al, 2004), are also targets of KLF4.…”
Section: P63 and Klf4 In Normal Skinmentioning
confidence: 99%
“…Profiling experiments have shown that KLF4 activates genes that inhibit proliferation, and represses genes that promote it Whitney et al, 2006;Swamynathan et al, 2008). However, studies on KLF4 in tumors suggest that its role is extremely complex and variegated.…”
mentioning
confidence: 99%
See 1 more Smart Citation